DESTINERRANCE. A VISUAL EXPERIENCE OF CROSSING EUROPE IN ALEXANDR SOKUROV’S ELEGY OF A VOYAGE (Analele Universității București. Limba și literatură română, 2024)
Starting from an analysis of Alexandr Sokurov’s documentary essay Elegy of a Voyage, this article proposes an examination of the experience of travel, of space-crossing, through the lens of a term that Jacques Derrida coined to define the ”postal principle”:destinerrance. Beyond merely testing the operational value of Derrida’s term, the analysis here aims to explore the formulas and the strategies Sokurov mobilizes to articulate visually the relationship between the ”suffering of the destination” (a journey acrossEurope from St. Petersburg to the Boijmans van Beuningen Museum in Rotterdam, in a difficult natural and cultural context) and its aesthetic expression (the nostalgia for a classical Europe that only survives in art).
Keywords: Derrida; journey; elegy; Sokurov